Welfare Costs of Risks and Management Options in Nigeria (2019)
Most of Nigeria’s declining welfare indicators such as poverty, food insecurity and life expectancy at birth have been linked to high risk exposure. However, little empirical investigations have been made to uncover the dynamics of risks and their attendant welfare implications at the household level using aggregate national data. This study thus investigated risk prevalence, its welfare cost and management strategies within households in Nigeria. Data from the Harmonised National Living Standard Survey (NLSS) of households, collected between 2009 and 2010 by the National Bureau of Statistics, provided the data set for the study. The results revealed that predominant shocks within households in Nigeria are the death of the household head, conflicts in the community, death of a spouse, the household head being away, spouse being away from home, household head hospitalized and personal theft. Among variables that significantly reduce households’ welfare were death and absence of the household head, and community conflict. Further, the results showed that the level of wealth significantly mitigates the negative impact of some shocks. Also, findings fromthe study revealed that households make use of mixed strategies to cope, mitigate and reduce risk exposure and impact. The study concluded by recommending provision of well-managed and need responsive socialinfrastructure suchas good health facilities, pipe-borne water, road network. In addition, people need to be sensitized to the need for life micro-assurance and government needs to subsidize it as this will help reduce the impact of the demise of the breadwinner on the household’s welfare.